Role of development strategy in New Uzbekistan - Suyunboyev Abbosbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in this article, a completely new national legal system is being formed in New Uzbekistan. That is, the principle of” Man, his rights, freedoms, especially value – the most important value " is recognized. Similar information.